Preparation method of graphene-like flaky powder material derived from polyimide film as well as product and application of graphene-like flaky powder material
By carbonizing, graphitizing and powdering the polyimide film, graphene-like flake powder material with excellent conductivity and obvious sheet structure was prepared, which solved the preparation difficulty and quality problems in the existing graphene preparation methods, and achieved simple and large-scale production.
Patent Information
- Application Number
- CN202411799551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing graphene preparation method has problems such as difficult preparation, harsh production conditions and unassurance of quality, and there is no method for preparing graphene-like sheet powder materials through polyimide films.
A polyimide film is used as a raw material and is carbonized, grinded and graphitized to produce a graphene-like flake powder material. The method includes post-treatment of the polyimide film, including carbonization, graphitization and powder making treatment, to obtain a graphene-like flake powder material with a distinct sheet structure and excellent conductivity.
The preparation of graphene-like sheet powder material has been realized, with obvious sheet structure and excellent conductivity, and the preparation process is simple and easy to produce on a large scale.
Smart Images

Figure CN119797344A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of graphene, and relates to a method for preparing a graphene-like flaky powder material derived from a polyimide film, and specifically relates to a method for preparing a graphene-like flaky powder material derived from a polyimide film, and a product and application thereof. Background Art
[0002] Graphene is a two-dimensional crystal composed of carbon atoms in the order of sp 2 Hybrid orbitals form a two-dimensional carbon nanomaterial with a hexagonal honeycomb lattice. Its unique structure gives it excellent electrical, mechanical, thermal and optical properties. These excellent physical properties make graphene have application potential in radio frequency transistors, ultra-sensitive sensors, flexible transparent conductive films, ultra-strong and high-conductivity composite materials, high-performance lithium-ion batteries and supercapacitors. The thickness of a single layer of graphene is only 0.335nm, which is one 200,000th of the diameter of a hair. As an ideal two-dimensional crystal material, the conductivity can reach 10 6 S / m. Graphene still has a certain application space in the fields of flexible screens, wearable devices, solar charging, etc. The rapid thermal conductivity and heat dissipation characteristics of graphene make graphene an excellent heat dissipation material, which can be used for heat dissipation of smart phones, tablets, high-power energy-saving LED lighting, satellite circuits, laser weapons, etc. Taking advantage of the advantages of graphene's ultra-thin and ultra-light, excellent electrochemical properties, high specific surface area, excellent electronic and ion conductivity, and special two-dimensional single atomic layer structure, it can be applied to power battery graphene negative electrode composite materials, lithium battery positive electrode conductive agents, and graphene functional coated aluminum foil, etc. It can also be used to reduce the weight of the battery and thus reduce the quality of the whole vehicle, extend the battery life, and greatly improve the range and charging speed of electric vehicles. Because graphene has high conductivity, it has also made breakthroughs in the fields of biosensors and aerospace military industry.
[0003] Previously, the preparation methods of graphene mainly include mechanical exfoliation, liquid phase exfoliation, chemical vapor deposition, redox method and electrochemical exfoliation. Mechanical exfoliation has the advantages of simple process preparation method and high sample quality, but the sample size is small and the number of layers cannot be controlled, so it can only be used for small-scale basic research in the laboratory. The samples prepared by the liquid phase exfoliation method are of high quality and few defects, but the sample yield is low, the size is small, the number of layers is large, and there are shortcomings such as solvent pollution and long preparation time. Chemical vapor deposition is currently a commonly used graphene preparation method, which can obtain samples with large sheet area, high quality and controllable number of layers, but the preparation process is complex, the cost is high and the preparation environment is harsh. Redox method is also a common preparation method, and the sample yield obtained is high and the cost is low, but this method has the disadvantages of incomplete sample structure and easy reduction pollution. The electrochemical exfoliation method has a short preparation time and mild reaction conditions, but the cost is high, the sample quality is low, and it cannot be mass-produced.
[0004] Although graphene has very excellent properties, it currently has various problems such as difficulty in preparation, harsh production conditions, and lack of quality assurance. In response to the above problems of graphene, further research is needed on materials that can replace graphene.
[0005] The invention patent with publication number CN113184842A discloses a method for preparing a highly graphitized graphite thick film, which comprises first preparing a polyimide film doped with a nanosheet material, and then sequentially subjecting the film to carbonization and graphitization to obtain a highly graphitized graphite thick film. The introduction of the nanosheet material helps to improve the degree of graphitization inside the polyimide film and improve the electrical and thermal conductivity of the finished graphite thick film, but the thickness of the polyimide film doped with the nanosheet material is 103-110 μm, and the thickness of the graphite thick film is 75-150 μm, both of which are relatively large and have a narrow application range.
[0006] The invention patent with publication number CN114437349A discloses a polyimide film, a preparation method thereof and a graphite film. The polyimide film includes a polyimide polymer, and the polyimide polymer includes a reaction product of a diamine monomer and a dianhydride monomer, and the diamine monomer includes N,N-bis(4-aminophenyl)-N,N-diphenyl-1,4-phenylenediamine. The preparation method of the polyimide film includes: adding a diamine monomer, a dianhydride monomer and a catalyst to an organic solvent, stirring the reaction under nitrogen protection to obtain a polyamic acid solution; performing imidization treatment on the polyamic acid solution to obtain the polyimide solution; coating the polyimide solution on a support plate to obtain a polyimide coating film; and baking and curing the polyimide coating film to obtain the polyimide film. The diamine monomer used has a large number of heat-resistant benzene ring structures, and the bonds between the benzene rings are nitrogen elements, so that the obtained polyimide polymer has a high carbon residual rate (high heat resistance), and thus the obtained polyimide film has a high carbon content after graphitization, so that the thickness of the graphitized polyimide film after calendering changes less, and thus a graphite film with a higher thickness can be obtained. The thickness of the polyimide film prepared in the invention is 50μm, which is relatively thick and has a narrow application range.
[0007] The invention patent with the publication number CN111470876B discloses a highly graphitized polyimide-based graphite thick film and a preparation method thereof. The preparation method of the highly graphitized polyimide-based graphite thick film comprises the following steps: preparing a carbon nanotube-doped polyimide thick film, then placing it in a carbonization furnace, carbonizing it at high temperature under an argon atmosphere, and finally transferring it to a graphite furnace for high-temperature graphitization, thereby obtaining a highly graphitized graphite thick film. The introduction of carbon nanotubes helps to improve the degree of graphitization of the polyimide thick film, and both the surface and the interior have a high degree of graphitization, which solves the problems of low film formation rate of the finished product and incomplete internal graphitization, thereby improving the thermal conductivity of the finished product. However, the thickness of the polyimide film in the invention is greater than 90 μm, which is relatively thick and has a narrow application range.
[0008] The polyimide film disclosed in the above technology is relatively thick, and no method for preparing a graphene-like flaky powder material through the polyimide film is disclosed. In view of the above problems, the present invention proposes a graphene-like flaky powder material, which has a distinct flaky structure and excellent conductive properties. Compared with the preparation of graphene, the graphene-like flaky powder material proposed in the present invention has a simpler preparation process. Summary of the invention
[0009] The present invention aims at the problems existing in the prior art and provides a method for preparing a graphene-like flaky powder material derived from a polyimide film, and its products and applications. The present invention adopts a polyimide film as a raw material, and obtains a graphene-like flaky powder material after carbonization, grinding and graphitization treatment. The graphene-like flaky powder material obtained after a series of treatments of a low-thickness polyimide film has an obvious flaky structure, a small particle size and excellent conductivity. The thickness of a single-layer graphene is 0.335nm. Compared with a single-layer graphene, the thickness of the graphene-like flaky powder material of the present invention is within the range of 0.05-5μm and also has excellent conductivity. Compared with the preparation process of a single-layer graphene, the preparation process of the graphene-like flaky powder material of the present invention is simple and easy to achieve large-scale production.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] In a first aspect, the present invention provides a method for preparing a graphene-like flaky powder material derived from a polyimide film, comprising the following steps:
[0012] The polyimide film is post-processed to obtain a graphene-like flaky powder material, wherein the post-processing includes carbonization, graphitization and powder making; the thickness of the polyimide film is 0.1-10 μm.
[0013] The D50 of the graphene-like flaky powder material prepared by the present invention is 0.2-50 μm, preferably 0.2-30 μm, more preferably 1.0-15 μm. The thickness of the graphene-like flaky powder material prepared is 0.05-5 μm, preferably 0.05-2.5 μm, more preferably 0.05-1.5 μm, most preferably 0.05-0.5 μm, and at this time has a clear flaky structure.
[0014] The sheet structure and conductivity of the prepared graphene-like flaky powder material are closely related to the thickness of the polyimide film raw material used. Under a specific particle size, the smaller the thickness of the polyimide film used, the more obvious its flaky structure, the higher the conductivity, and the larger the contact area of the graphene-like flaky powder material with the active material when used as a conductive agent, and the easier it is to form a stable conductive network. When the particle size of the graphene-like flaky powder material is less than 0.2μm, it is easy to agglomerate, which greatly limits its application; when the particle size is greater than 50μm, it cannot be evenly dispersed during use, and it cannot be well mixed with other conductive materials, which will have an unpredictable impact on the performance of the material. When used as an electrode material to prepare an electrode, the prepared electrode is not tight enough, and the contact resistance will increase significantly, which indirectly affects the conductive properties of the graphene-like flaky powder material.
[0015] Specifically, the present invention uses a polyimide film as a raw material and performs post-processing as a carbon source to obtain a graphene-like flaky powder material. The thickness of the polyimide film is 0.1-10 μm, preferably 0.1-5 μm, more preferably 0.1-3 μm, further preferably 0.1-1 μm, and most preferably greater than or equal to 0.1 μm and less than 1 μm. When the thickness of the polyimide film is less than 0.1 μm, its production cost is high and difficult. When the thickness of the polyimide film is greater than 10 μm, the obtained powder is a graphite powder with low conductivity.
[0016] Among them, polyimide refers to a class of polymers containing imide rings, which are formed by the gradual polymerization reaction of dianhydride and diamine monomers. Its molecular chain contains a large number of rigid benzene ring structures. There is a conjugation effect between the lone pair of electrons of the nitrogen atom on the imide ring and the π electrons of the carbonyl group. Its structure is regular and mostly a two-dimensional planar structure. It has the advantages of strong chemical stability and excellent heat resistance. The carbon content of polyimide itself is high, usually reaching more than 60%. In addition, its purity is also high. Except for common elements such as C, H, O, and N, there are generally no other elements. It is a good carbon source. In addition, the polyimide film is a two-dimensional planar structure, which plays a key role in the flaky structure of the powder material as a carbon source.
[0017] The method for preparing the polyimide film is to prepare the polyimide film by a single-layer method or a multi-layer method, and the steps of preparing the polyimide film by the single-layer method include:
[0018] The diamine monomer and the dianhydride monomer are dissolved in a non-protonic organic solvent to react to obtain a polyamic acid solution, and the polyamic acid solution is cast, dried and imidized to obtain a single-layer polyimide film; wherein the polyimide is a thermosetting polyimide;
[0019] The diamine monomer includes one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine, 3,4'-diaminodiphenyl ether, methylphenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfonamide, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 1,4-bis(3-methyl-5-aminophenyl)benzene and amide-forming derivatives thereof; preferably one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine and 3,4'-diaminodiphenyl ether; in one embodiment, the diamine monomer is selected from 4,4'-diaminodiphenyl ether and p-phenylenediamine, and the molar ratio of the 4,4'-diaminodiphenyl ether to p-phenylenediamine is preferably 1-3:1, more preferably 2.3:1;
[0020] The dianhydride monomer includes one or more of 1,2,4,5-benzenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane tetracarboxylic dianhydride, and 2,2'-bis(3,4-dicarboxyphenoxy)hexafluoropropane tetracarboxylic dianhydride; preferably one or two of 1,2,4,5-benzenetetracarboxylic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride;
[0021] The imidization may be carried out by thermal imidization or catalytic method, and the catalyst used in the catalytic method includes but is not limited to one or more of alicyclic tertiary amines or fully aromatic tertiary amine catalysts such as quinoline, isoquinoline, pyridine, N-methylpiperidine, 1,4-diazabicyclo[2,2,2]octane, 1,5-diazabicyclo[4,3,0]-5-nonene, 1,8-diazabicyclo[5,4,0]-7-undecene;
[0022] Alternatively, a diamine monomer and a dianhydride monomer are dissolved in a solvent, and then a catalyst and a dehydrating agent are added to react to obtain a polyimide solution, and the polyimide solution is cast and dried to obtain a single-layer polyimide film; wherein the polyimide is a thermoplastic polyimide;
[0023] The diamine monomer includes one or more of 2,4'-diaminobenzophenone, 2,4'-diaminodiphenylmethane, 2,4'-diaminodiphenyl ether, 3,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, and 1,3-phenylenediamine, preferably one or more of 2,4'-diaminobenzophenone, 2,4'-diaminodiphenylmethane, and 2,4'-diaminodiphenyl ether; in one embodiment, the diamine monomer is selected from 2,4'-diaminobenzophenone;
[0024] The dianhydride monomer includes one or more of 4,4-hexafluoroisopropylphthalic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 5-[4-(1,3-dioxo-2-benzofuran-5-yl)phenyl]-2-benzofuran-1,3-dione, and preferably one or more of 4,4-hexafluoroisopropylphthalic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, and 3,3',4,4'-diphenylsulfone tetracarboxylic anhydride.
[0025] In one embodiment, the method for preparing the polyimide film is to prepare the polyimide film by a single-layer method, wherein the polyimide is a thermosetting polyimide, and the preparation method comprises the following steps:
[0026] 1) preparing a polyamic acid precursor, wherein the preparation method of the polyamic acid precursor can adopt any method known to those skilled in the art, wherein a diamine monomer can be dissolved or dispersed in an aprotic organic solvent, and then a dianhydride monomer in an equimolar ratio with the diamine monomer is added for polymerization to obtain an aprotic organic solution of the polyamic acid precursor; or a small amount of diamine monomer can be reacted with a dianhydride monomer in an aprotic organic solvent to obtain a prepolymer, and then the dianhydride monomer is slowly added to the prepolymer to polymerize the dianhydride monomer and the diamine monomer in an equimolar ratio to obtain an aprotic organic solution of the polyamic acid precursor; or a dianhydride monomer can be reacted with a small amount of diamine monomer in an aprotic organic solvent to obtain a prepolymer, and then the diamine monomer is added to the prepolymer to polymerize the dianhydride monomer and the diamine monomer in an equimolar ratio to obtain an aprotic organic solution of the polyamic acid precursor.
[0027] The aprotic organic solvent includes, but is not limited to, one or more of acetamide solvents, formamide solvents, phenylacetone solvents, phenol solvents, sulfite solvents, aprotic polar solvents and aromatic hydrocarbon solvents.
[0028] The acetamide solvent may be one or both of N,N-dimethylacetamide and N,N-diethylacetamide.
[0029] The formamide solvent may be one or both of N,N-dimethylformamide and N,N-diethylformamide.
[0030] The propiophenone solvent may be one or both of N-methyl-2-propenone and N-vinyl-2-propenone.
[0031] The phenolic solvent may be one or more of phenol, o-cresol, m-cresol, p-cresol, xylenol, halogenated phenol and catechol.
[0032] The sulfite solvent may be one or more of dimethyl sulfite and diethyl sulfite co-oxide.
[0033] The aprotic polar solvent may be one or both of hexamethylphosphoramide and γ-butyrolactone.
[0034] The aromatic hydrocarbon solvent may be one or more of xylene and toluene.
[0035] Preferably, the aprotic organic solvent is selected from acetamide solvents or formamide solvents.
[0036] 2) treating a non-protonic organic solution of a polyamic acid precursor onto a support, wherein the treatment includes but is not limited to a salivation method, a salivation-biaxial stretching method, a dipping method, a spin coating method, a vapor deposition method or a spraying method, preferably a salivation method, curing the solution and performing imidization to obtain a single-layer polyimide film, wherein the curing process includes a thermal curing method and a catalyst method.
[0037] The thermal curing method preferably adopts a gradient temperature increase, and the gradient temperature is preferably 200-300° C. In one embodiment, the gradient temperature is 200° C. for 30 min, 250° C. for 30 min, and 300° C. for 1 h.
[0038] The catalyst method requires the addition of a catalyst and a dehydrating agent to the non-protonic organic solution of the polyamic acid precursor, and then the solution is treated on a support, and then the temperature is increased gradually for treatment; the catalyst used includes, but is not limited to, one or more of alicyclic tertiary amines or fully aromatic tertiary amine catalysts, and may be one or more of quinoline, isoquinoline, pyridine, N-methylpiperidine, 1,4-diazabicyclo[2,2,2]octane, 1,5-diazabicyclo[4,3,0]-5-nonene and 1,8-diazabicyclo[5,4,0]-7-undecene. The dehydrating agent used includes, but is not limited to, acetic anhydride, anhydrous propionic acid, aliphatic carboxylic anhydrides such as anhydrous citric acid, and aromatic carboxylic anhydrides such as benzoic anhydride, wherein acetic anhydride and / or benzoic anhydride are preferred.
[0039] In one embodiment, the method for preparing the polyimide film is to prepare the polyimide film by a single-layer method, wherein the polyimide is a thermoplastic polyimide, and the preparation method comprises the following steps:
[0040] Under nitrogen conditions, dianhydride monomer and diamine monomer are used as raw materials, corresponding catalysts and dehydrating agents are added, and polycondensation reaction is carried out in a high boiling point solvent at high temperature to obtain a polyimide solution, and then the polyimide solution is formed on a support by a salivation method, a salivation-biaxial stretching method, an immersion method, a spin coating method, an evaporation method or a spraying method to obtain a single-layer polyimide film. The high boiling point solvent includes but is not limited to one or more of aprotic organic solvents, phenolic solvents, ketone solvents and polar solvents.
[0041] The aprotic organic solvent may be one or more of N-methyl-2-pyrrolidone, N,N-dimethylacetamide and 1,4-butyrolactone.
[0042] The phenolic solvent may be one or more of chlorophenol and cresol.
[0043] The ketone may be cyclohexanone.
[0044] The polar solvent may be one or more of tetrahydrofuran, chloroform and dichloromethane.
[0045] The high boiling point solvent is preferably one or more of an aprotic organic solvent and a phenolic solvent.
[0046] The catalyst and dehydrating agent are used in the polycondensation reaction, and the catalyst includes but is not limited to one or more of alicyclic tertiary amines or fully aromatic tertiary amines, and can be one or more of quinoline, isoquinoline, pyridine, N-methylpiperidine, 1,4-diazabicyclo[2,2,2]octane, 1,5-diazabicyclo[4,3,0]-5-nonene and 1,8-diazabicyclo[5,4,0]-7-undecene. The dehydrating agent used in the polycondensation reaction includes but is not limited to one or more of acetic anhydride, anhydrous propionic acid, aliphatic carboxylic acid anhydride and aromatic carboxylic acid anhydride, the aliphatic carboxylic acid anhydride includes but is not limited to anhydrous citric acid, the aromatic carboxylic acid anhydride includes but is not limited to benzoic anhydride, wherein the dehydrating agent is preferably acetic anhydride and / or benzoic anhydride.
[0047] In one embodiment, the method for preparing the polyimide film is to prepare the polyimide film by a multilayer method, and the steps of preparing the polyimide film by the multilayer method include:
[0048] 1) preparing a single-layer polyimide film according to the single-layer polyimide film preparation step;
[0049] 2) coating a release agent on the surface of the obtained polyimide film; preparing a single-layer polyimide film on the surface of the release agent according to step 1);
[0050] 3) Repeat step 2) to obtain a multi-layer polyimide film.
[0051] The number of layers of the multilayer polyimide film is not limited here, and it is convenient for collection. The release agent is used to separate the polyimide film layers during the preparation process, and there is no residue in the graphene-like flaky powder material, and it will not affect the structure of the graphene-like flaky powder material prepared by the polyimide film in the present invention. The release agent can be selected from any release agent known to those skilled in the art, including but not limited to silicone oil series release agents such as polydimethylsiloxane, fluoride series release agents such as polytetrafluoroethylene, polyurethane, polyvinyl alcohol, etc. In the preparation step of the multilayer polyimide film, in order to facilitate peeling and collection from the support, the thickness of the single-layer polyimide film is 0.1-10μm, preferably greater than or equal to 0.1μm and less than 1μm.
[0052] Preferably, in order to facilitate the graphitization of the polyimide film in the subsequent process, an appropriate amount of filler can be added during the preparation of the polyimide film to improve the degree of graphitization. The filler includes but is not limited to one or more of nano-scale metal oxides, nano-scale silicon oxides and nano-scale inorganic substances. The nano-scale metal oxide can be one or more of aluminum oxide, vanadium pentoxide and titanium dioxide. The nano-scale silicon oxide can be silicon dioxide. The nano-scale inorganic substance can be one or more of calcium phosphate, calcium hydrogen phosphate and calcium pyrophosphate.
[0053] The polyimide film is post-processed to obtain a graphene-like flaky powder material, and the post-processing includes carbonization, graphitization and powder making. The present invention does not limit the sequence of the carbonization, graphitization and powder making processes, and the carbonization is before graphitization. There is no requirement for the sequence and number of powder making processes, and the powder making process can be performed before carbonization, after carbonization and before graphitization, or after graphitization.
[0054] The carbonization is carried out under vacuum conditions at a temperature of 1100-1400°C. During the carbonization process, there is no special setting for the heating rate during heating, and it is preferably carried out in a continuous heating or gradient heating manner. In one embodiment, the carbonization process is specifically as follows: under vacuum conditions, the temperature is raised from room temperature to 1300°C at a rate of 5°C / min, and after being kept constant for 1h, the temperature is lowered to room temperature at a rate of 15°C / min.
[0055] The graphitization is carried out in an inert gas, and the inert gas is preferably argon. The temperature of graphitization is 2400-3300°C, preferably 2700-3300°C, and more preferably 2800-3300°C. During the graphitization process, there is no special setting for the heating rate during heating, and it is preferably carried out in a continuous heating or gradient heating manner. The higher the graphitization temperature, the higher the degree of graphitization, the better the crystallization order of the material, and the higher the quality of the graphite obtained, but the cost of preparation will also increase exponentially accordingly. In one embodiment, the graphitization process is specifically as follows: under argon conditions, the temperature is increased from room temperature to 2800°C at a rate of 3°C / min, and after constant temperature for 1h, the temperature is reduced to room temperature at a rate of 10°C / min.
[0056] The powder making process can be any known powder making process, which is not limited here, including but not limited to ball milling, bead milling, sand milling, air flow milling, vibration milling, colloid milling and other powder making methods.
[0057] In one embodiment, a method for preparing a graphene-like flaky powder material includes: a polyimide film is subjected to a pulverizing treatment to obtain a polyimide powder, the polyimide powder is placed in a carbonization furnace for carbonization to obtain carbon powder, and the carbon powder is placed in a graphite furnace for graphitization to obtain a graphene-like flaky powder material; the carbon powder can also be graphitized after the pulverizing treatment to obtain a graphene-like flaky powder material.
[0058] In one embodiment, a method for preparing a graphene-like flaky powder material includes: carbonizing a polyimide film in a carbonization furnace to obtain a carbon film, subjecting the carbon film to a pulverizing process to obtain carbon powder, and placing the carbon powder in a graphite furnace for graphitization to obtain a graphene-like flaky powder material.
[0059] In one embodiment, a method for preparing a graphene-like flaky powder material includes: carbonizing a polyimide film in a carbonization furnace to obtain a carbon film, placing the carbon film in a graphite furnace for graphitization to obtain a graphite film, and powdering the graphite film to obtain a graphene-like flaky powder material.
[0060] In a second aspect, the present invention provides a graphene-like flaky powder material prepared by the preparation method described in the above technical solution.
[0061] In a third aspect, the present invention provides an application of a graphene-like flaky powder material prepared by the preparation method described in the above technical solution in electronic devices or batteries.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] First, the graphene-like flaky powder material prepared by the present invention using polyimide film has a distinct flaky structure and high purity. Compared with single-layer graphene, the graphene-like flaky powder material of the present invention also has excellent conductivity in the thickness range of 0.05-5μm, and can be used as a conductive agent in the preparation of battery electrodes to improve the conductivity, first-cycle discharge specific capacity and cycle performance of the battery.
[0064] Secondly, the graphene-like flaky powder material can be used as an additive in various composite materials to increase the electrical conductivity, thermal conductivity, conduction, antistatic and other properties of the composite materials.
[0065] Third, compared with the preparation process of graphene, the process of preparing graphene-like flaky powder materials of the present invention is simple, easy to achieve large-scale production, and can be applied to the field of conductive materials as an additive to improve the conductive properties of materials.
[0066] Fourthly, different types of diamine monomers and dianhydride monomers in the present invention are used to prepare polyimide using different preparation methods, and the graphene-like flaky powder materials further prepared have good conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a process diagram for preparing a graphene-like flake powder material based on a polyimide film;
[0068] Figure 2 The graphene-like flake powder material P prepared in Example 1 1-1 SEM images of
[0069] Figure 3 The graphene-like flake powder material P prepared in Example 6 6-1 SEM image of . DETAILED DESCRIPTION
[0070] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0071] As an example illustration:
[0072] Button cell separator, positive electrode shell, negative electrode shell, gasket and spring sheet (all battery grade, Guangdong Candlelight New Energy Company).
[0073] The present invention is described below through specific embodiments to make the technical solution of the present invention easier to understand and grasp, but the present invention is not limited thereto, and the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0074] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0075] The preparation process of the graphene-like flake powder material based on the polyimide film of the present invention is as follows: Figure 1 As shown, specifically: first prepare a single-layer PI (polyimide) film, carbonize it to obtain a single-layer carbon film, then graphitize it to obtain a single-layer graphite film, and finally grind it into powder to obtain a graphene-like flaky powder material; or, first prepare a multilayer PI (polyimide) film, the multilayer PI film consists of n layers of single-layer PI films and a release agent located between the layers, the multilayer PI film is carbonized to obtain a multilayer carbon film, then graphitize it to obtain a multilayer graphite film, and finally grind it into powder to obtain a graphene-like flaky powder material.
[0076] The relevant performance test / calculation methods in the present invention are as follows:
[0077] 1. Particle size test: The particle size test was performed using a laser particle size analyzer Mastersizer 2000 and distilled water as a dispersant. The reference "Equivalent Particle Size of Rod-Shaped and Flake-Shaped Particles in Laser Particle Size Analyzer (I) - Theory and Calculation Model" mentioned that non-spherical particles are neither equivalent to spherical particles of equal volume nor to spherical particles of a certain other single diameter in a laser particle size analyzer. The diameter of the flake particles determines the particle size D50 of the equivalent particle size, and the thickness does not affect the particle size D50. This shows that the particle size D50 in the test results of the laser particle size analyzer can represent the size on the surface of the flake particles. In the present invention, the particle size D50 in the test results of the laser particle size analyzer is used as the particle size of the flake conductive powder material.
[0078] 2. Polyimide film thickness test: The ultra-thin polyimide film is tested using an M-2000v ellipsometer.
[0079] 3. Conductivity test: The four-probe method is used to test the powder "resistivity-pressure", conductivity = 1 / resistivity. The sample carbon powder is pressed into a sample with a certain thickness by a tablet press. Four electrodes are connected to the current source and the voltmeter. The two units are connected to the powder sample from independent circuits. During the test, a pressure of 10MPa is applied to perform conductivity testing.
[0080] 4. SEM detection: Czech TESCAN MIRA LMS testing equipment is used to characterize the appearance and morphology of the samples.
[0081] 5. Conductivity growth rate calculation formula:
[0082] Conductivity growth rate (%) = 100*conductivity growth / original conductivity.
[0083] Description of the embodiments: Embodiments 1-9 are for preparing PI (polyimide) films using PAA (polyamic acid) resin solution; Embodiments 10-14 are for preparing PI films using thermoplastic polyimide solution; Embodiments 15-16 are two other processes for preparing graphene-like flaky powder materials.
[0084] Example 1
[0085] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 9.327 g (46.58 mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159 g (19.96 mmol) of p-phenylenediamine (PDA), and 174.0 g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred uniformly at room temperature. Then, 14.52 g (66.56 mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30 min-1 h. After the addition was completed, the reaction was stirred for 1 h to obtain a polyamic acid (PAA) resin solution. A glass sheet was used as a support to spin-coat the polyamic acid resin solution on a coater, and the solution was placed in a vacuum drying oven to dry and remove the solvent. The solution was then placed in a high-temperature oven and heated in a gradient manner at 200°C for 30 min, 250°C for 30 min, and 300°C for 1 h. After thermal imidization under high temperature conditions, a single-layer polyimide film with a thickness of 0.1 μm was obtained by controlling the process.
[0086] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.1 μm was prepared on the surface of the release agent according to step 1).
[0087] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0088] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and under vacuum conditions, the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion, and the speed is set to 1200rpm. By controlling the grinding time, two types of carbon powder with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powder with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 1-1 and P 1-2 (particle size D50 is about 10μm and 20μm respectively), P 1-1 The SEM images are as follows Figure 2 shown.
[0089] Example 2
[0090] The difference from Example 1 is that the thickness of the single-layer polyimide film is 0.3 μm, as follows:
[0091] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 9.327 g (46.58 mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159 g (19.96 mmol) of p-phenylenediamine (PDA), and 174.0 g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred uniformly at room temperature. Then, 14.52 g (66.56 mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30 min-1 h. After the addition was completed, the reaction was stirred for 1 h to obtain a polyamic acid (PAA) resin solution. A glass sheet was used as a support to spin-coat the polyamic acid resin solution on a coater, and the solution was placed in a vacuum drying oven to dry and remove the solvent. The solution was then placed in a high-temperature oven and heated in a gradient manner at 200°C for 30 min, 250°C for 30 min, and 300°C for 1 h. After thermal imidization under high temperature conditions, a single-layer polyimide film with a thickness of 0.3 μm was obtained by controlling the process.
[0092] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.3 μm was prepared on the surface of the release agent according to step 1).
[0093] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0094] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and under vacuum conditions, the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion, and the speed is set to 1200rpm. By controlling the grinding time, two types of carbon powder with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powder with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 2-1 and P 2-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0095] Example 3
[0096] The difference from Example 1 is that the thickness of the single-layer polyimide film is 0.5 μm, specifically as follows:
[0097] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 9.327 g (46.58 mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159 g (19.96 mmol) of p-phenylenediamine (PDA), and 174.0 g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred uniformly at room temperature. Then, 14.52 g (66.56 mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30 min-1 h. After the addition was completed, the reaction was stirred for 1 h to obtain a polyamic acid (PAA) resin solution. A glass sheet was used as a support to spin coat the polyamic acid resin solution on a coater, and the solution was placed in a vacuum drying oven to dry and remove the solvent. The solution was then placed in a high-temperature oven and heated in a gradient manner at 200°C for 30 min, 250°C for 30 min, and 300°C for 1 h. After thermal imidization under high temperature conditions, a single-layer polyimide film with a thickness of 0.5 μm was obtained by controlling the process.
[0098] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.5 μm was prepared on the surface of the release agent according to step 1).
[0099] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0100] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and under vacuum conditions, the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion, and the speed is set to 1200rpm. By controlling the grinding time, two types of carbon powder with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powder with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 3-1 and P 3-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0101] Example 4
[0102] The difference from Example 1 is that the thickness of the single-layer polyimide film is 0.7 μm, specifically as follows:
[0103] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 9.327 g (46.58 mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159 g (19.96 mmol) of p-phenylenediamine (PDA), and 174.0 g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred uniformly at room temperature. Then, 14.52 g (66.56 mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30 min-1 h. After the addition was completed, the reaction was stirred for 1 h to obtain a polyamic acid (PAA) resin solution. A glass sheet was used as a support to spin coat the polyamic acid resin solution on a coater, and the solution was placed in a vacuum drying oven to dry and remove the solvent. The solution was then placed in a high-temperature oven and heated in a gradient manner at 200°C for 30 min, 250°C for 30 min, and 300°C for 1 h. After thermal imidization under high temperature conditions, a single-layer polyimide film with a thickness of 0.7 μm was obtained by controlling the process.
[0104] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.7 μm was prepared on the surface of the release agent according to step 1).
[0105] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0106] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and under vacuum conditions, the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion, and the speed is set to 1200rpm. By controlling the grinding time, two types of carbon powder with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powder with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 4-1 and P 4-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0107] Example 5
[0108] The difference from Example 1 is that the thickness of the single-layer polyimide film is 0.9 μm, specifically as follows:
[0109] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 9.327 g (46.58 mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159 g (19.96 mmol) of p-phenylenediamine (PDA), and 174.0 g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred uniformly at room temperature. Then, 14.52 g (66.56 mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30 min-1 h. After the addition was completed, the reaction was stirred for 1 h to obtain a polyamic acid (PAA) resin solution. A glass sheet was used as a support to spin coat the polyamic acid resin solution on a coater, and the solution was placed in a vacuum drying oven to dry and remove the solvent. The solution was then placed in a high-temperature oven and heated in a gradient manner at 200°C for 30 min, 250°C for 30 min, and 300°C for 1 h. After thermal imidization under high temperature conditions, a single-layer polyimide film with a thickness of 0.9 μm was obtained by controlling the process.
[0110] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.9 μm was prepared on the surface of the release agent according to step 1).
[0111] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0112] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and under vacuum conditions, the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion, and the speed is set to 1200rpm. By controlling the grinding time, two types of carbon powder with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept at a constant temperature for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powder with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 5-1 and P 5-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0113] Example 6
[0114] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, dried in a vacuum drying oven, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 1 μm was obtained by controlling the process.
[0115] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and under vacuum conditions, the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept at constant temperature for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two types of carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min, and after being kept at constant temperature for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 6-1 and P 6-2 (particle size D50 is about 10μm and 20μm respectively), P 2-1 The SEM images are as follows Figure 3 shown.
[0116] Example 7
[0117] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 3 μm was obtained by controlling the process.
[0118] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two types of carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two types of graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 7-1 and P 7-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0119] Example 8
[0120] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 5 μm was obtained by controlling the process.
[0121] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and under vacuum conditions, the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min, and after being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 8-1 and P 8-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0122] Example 9
[0123] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 10 μm was obtained by controlling the process.
[0124] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and under vacuum conditions, the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min, and after being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min, and after being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain graphene-like flake powder materials, which were numbered P 9-1 and P 9-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0125] Example 10
[0126] 1) In a 500 mL three-necked flask equipped with a rotary stirrer, 12.74 g (60.02 mmol) of 2,4'-diaminobenzophenone and 263.61 g of N-methyl-2-pyrrolidone (NMP) were added under high temperature conditions in a nitrogen atmosphere, and the mixture was stirred uniformly at room temperature. Then, 26.65 g (59.99 mmol) of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added in batches within 30 min-1 h. After stirring uniformly, an equal molar amount of isoquinoline to 4,4-hexafluoroisopropylphthalic anhydride (6FDA) and a twice molar amount of acetic anhydride to 4,4-hexafluoroisopropylphthalic anhydride (6FDA) were added, and the reaction was stirred for 1 h to obtain a polyimide solution. The polyimide solution was spin-coated on a coater using a glass sheet as a support, and then placed in a vacuum drying oven for drying to remove the solvent and complete curing. A single-layer polyimide film with a thickness of 0.1 μm was obtained by controlling the coater process.
[0127] 2) To facilitate peeling, a layer of release agent (polyvinyl alcohol) was subsequently coated on the surface of the obtained single-layer polyimide film, and then a single-layer polyimide film with a thickness of 0.1 μm was prepared on the surface of the release agent according to step 1).
[0128] 3) Repeat step 2) for 48 times to obtain a 50-layer polyimide film.
[0129] 4) The 50-layer polyimide film prepared above is placed in a carbonization furnace, the maximum temperature of the carbonization furnace is set to 1300°C, and the temperature is raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature is lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film is simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm are added in a certain proportion. The speed is set to 1200rpm, and two carbon powders with different particle sizes (D50 is about 10μm and 20μm, respectively) are obtained by controlling the grinding time. The obtained carbon powders are placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature is lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 10-1 and P 10-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0130] Embodiment 11
[0131] In a 500mL three-necked flask equipped with a rotary stirrer, 12.74g (60.02mmol) of 2,4'-diaminobenzophenone and 263.61g of N-methyl-2-pyrrolidone (NMP) were added under high temperature conditions in a nitrogen atmosphere, and the mixture was stirred evenly at room temperature. Then, 26.65g (59.99mmol) of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added in batches within 30min-1h. After stirring evenly, 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added with an equal molar amount of isoquinoline and 4,4-hexafluoroisopropylphthalic anhydride (6FDA) twice the molar amount of acetic anhydride, and the reaction was stirred for 1h to obtain a polyimide solution. The polyimide solution was dried in a drying oven to remove the solvent by salivation and drying to obtain a polyimide film. A polyimide film with a thickness of 1μm was obtained by controlling the process.
[0132] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 11-1 and P 11-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0133] Example 12
[0134] In a 500mL three-necked flask equipped with a rotary stirrer, 12.74g (60.02mmol) of 2,4'-diaminobenzophenone and 263.61g of N-methyl-2-pyrrolidone (NMP) were added under high temperature conditions in a nitrogen atmosphere, and the mixture was stirred evenly at room temperature. Then, 26.65g (59.99mmol) of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added in batches within 30min-1h. After stirring evenly, 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added with an equal molar amount of isoquinoline and 4,4-hexafluoroisopropylphthalic anhydride (6FDA) twice the molar amount of acetic anhydride, and the reaction was stirred for 1h to obtain a polyimide solution. The polyimide solution was drooled and dried in a drying oven to remove the solvent to obtain a polyimide film. A polyimide film with a thickness of 3μm was obtained by controlling the process.
[0135] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 12-1 and P 12-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0136] Example 13
[0137] In a 500mL three-necked flask equipped with a rotary stirrer, 12.74g (60.02mmol) of 2,4'-diaminobenzophenone and 263.61g of N-methyl-2-pyrrolidone (NMP) were added under high temperature conditions in a nitrogen atmosphere, and the mixture was stirred evenly at room temperature. Then, 26.65g (59.99mmol) of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added in batches within 30min-1h. After stirring evenly, 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added with an equal molar amount of isoquinoline and 4,4-hexafluoroisopropylphthalic anhydride (6FDA) twice the molar amount of acetic anhydride, and the reaction was stirred for 1h to obtain a polyimide solution. The polyimide solution was drooled and dried in a drying oven to remove the solvent to obtain a polyimide film. A polyimide film with a thickness of 5μm was obtained by controlling the process.
[0138] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 13-1 and P 13-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0139] Embodiment 14
[0140] In a 500mL three-necked flask equipped with a rotary stirrer, 12.74g (60.02mmol) of 2,4'-diaminobenzophenone and 263.61g of N-methyl-2-pyrrolidone (NMP) were added under high temperature conditions in a nitrogen atmosphere, and the mixture was stirred evenly at room temperature. Then, 26.65g (59.99mmol) of 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added in batches within 30min-1h. After stirring evenly, 4,4-hexafluoroisopropylphthalic anhydride (6FDA) was added with an equal molar amount of isoquinoline and 4,4-hexafluoroisopropylphthalic anhydride (6FDA) twice the molar amount of acetic anhydride, and the reaction was stirred for 1h to obtain a polyimide solution. The polyimide solution was dried in a salivating oven to remove the solvent to obtain a polyimide film. A polyimide film with a thickness of 10μm was obtained by controlling the process.
[0141] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 14-1 and P 14-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0142] Embodiment 15
[0143] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 3 μm was obtained by controlling the process.
[0144] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The obtained carbon film was simply cut, placed in a graphitization mold, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain a graphite film. The graphite film was placed in a planetary ball mill for ball milling, and zirconium oxide beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion. The speed was set to 1200rpm, and two graphite powders with uniform particle sizes (D50 was approximately 10μm and 20μm, respectively) were obtained by controlling the grinding time. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain two graphene-like flake powder materials, which were numbered P 15-1 and P 15-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0145] Example 16
[0146] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 3 μm was obtained by controlling the process.
[0147] The polyimide film prepared above was simply crushed and then put into a planetary ball mill for ball milling. Zirconia beads with diameters of 20 mm, 10 mm, 5 mm and 1 mm were added in a certain proportion, and the rotation speed was set to 2000 rpm to obtain polyimide powder. The polyimide powder material was placed in a carbonization furnace, and the maximum temperature of the carbonization furnace was set to 1300 ° C. Under vacuum conditions, the temperature was raised from room temperature 25 ° C to 1300 ° C at a rate of 5 ° C / min. After constant temperature for 1 hour, the temperature was lowered to room temperature 25 ° C at a rate of 15 ° C / min to obtain carbon powder. The obtained carbon powder was put into a planetary ball mill for ball milling. Zirconia beads with diameters of 20 mm, 10 mm, 5 mm and 1 mm were added in a certain proportion. The rotation speed was set to 1200 rpm. By controlling the grinding time, two carbon powders with uniform particle sizes (D50 was about 10 μm and 20 μm, respectively) were obtained. The two carbon powders were placed in a graphitization mold and graphitized under argon conditions. The temperature was raised from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1MPa) at 150°C and dried for 12h to obtain two graphene-like flake powder materials, which were numbered P 16-1 and P 16-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0148] Comparative Example 1
[0149] Compared with Example 1-5, the only difference is the thickness of the polyimide film, as follows:
[0150] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 20 μm was obtained by controlling the process.
[0151] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, the speed was set to 1200rpm, and two carbon powders with different particle sizes were obtained by controlling the grinding time. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes (D50 was about 10μm and 20μm, respectively). The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) at 150 °C and dried for 12 h to obtain two graphite powder materials, which were numbered P D1-1 and P D1-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0152] Comparative Example 2
[0153] Compared with Examples 1-5, the only difference is the thickness of the polyimide film, as follows:
[0154] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 50 μm was obtained by controlling the process.
[0155] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. By controlling the grinding time, two carbon powders with different particle sizes (D50 was about 10μm and 20μm, respectively) were obtained. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes. The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) at 150 °C and dried for 12 h to obtain two graphite powder materials, which were numbered P D2-1 and P D2-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0156] Comparative Example 3
[0157] Compared with Examples 1-5, the only difference is the thickness of the polyimide film, as follows:
[0158] In a 500mL three-necked flask equipped with a rotary stirrer, 9.327g (46.58mmol) of 4,4'-diaminodiphenyl ether (ODA), 2.159g (19.96mmol) of p-phenylenediamine (PDA), and 174.0g of N,N-dimethylacetamide (DMAC) were added, and the mixture was stirred evenly at room temperature, and then 14.52g (66.56mmol) of 1,2,4,5-benzenetetracarboxylic dianhydride (PMDA) was added in batches within 30min-1h. After the addition was completed, the reaction was stirred for 1h to obtain a polyamic acid (PAA) resin solution. The polyamic acid resin solution was poured onto a glass plate, placed in a vacuum drying oven to dry, the solvent was removed, and then placed in a high-temperature oven, and the temperature was increased gradually according to 200℃ for 30min, 250℃ for 30min, and 300℃ for 1h, and a polyimide film was obtained by thermal imidization under high temperature conditions. A polyimide film with a thickness of 100 μm was prepared by controlling the process.
[0159] The polyimide film prepared above was placed in a carbonization furnace, the maximum temperature of the carbonization furnace was set to 1300°C, and the temperature was raised from room temperature 25°C to 1300°C at a rate of 5°C / min under vacuum conditions. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 15°C / min to obtain a carbon film. The carbon film was simply crushed and then placed in a planetary ball mill for ball milling. Zirconia beads with diameters of 20mm, 10mm, 5mm and 1mm were added in a certain proportion, and the speed was set to 1200rpm. Carbon powders of two particle sizes were obtained by controlling the grinding time. The obtained carbon powders were placed in graphitization molds, graphitized under argon conditions, and heated from room temperature 25°C to 2800°C at a rate of 3°C / min. After being kept constant for 1h, the temperature was lowered to room temperature 25°C at a rate of 10°C / min to obtain two graphite powders with uniform particle sizes (D50 was about 10μm and 20μm, respectively). The two graphite powders were placed in a vacuum drying oven (gauge pressure of -0.1 MPa) and dried at 150 °C for 12 h to obtain graphite powder materials, which were numbered P D3-1 and P D3-2 (Particle size D50 is approximately 10μm and 20μm respectively).
[0160] Test Example 1
[0161] The "resistivity-pressure" of the powder was tested by the four-probe method, where conductivity = 1 / resistivity. The samples were: the graphene-like flake powder material obtained in Examples 1-16 and the graphite powder material obtained in Comparative Examples 1-3, prepared under the same applied pressure. Four electrodes were connected to the current source and the voltmeter, and the two units were connected to the sample from independent circuits. During the test, the pressure applied was 10 MPa, and the conductivity test was performed. The test results of each group are shown in Table 1.
[0162] Table 1 Sample performance test results
[0163]
[0164]
[0165] The results in Table 1 show that, from Examples 1-9, it is found that under the condition of a specific particle size D50, as the thickness of the single-layer polyimide film increases, the conductivity and degree of graphitization of the graphene-like flaky powder material decrease in turn. This is mainly because when the thickness of the single-layer polyimide film increases, the thickness of the flaky structure powder also increases at the microscopic level, the conductive performance decreases, and the conductivity decreases. The same rule is also found in Examples 10-16.
[0166] In Examples 1-16, it can be seen that under the same thickness of the single-layer polyimide film and the specific particle size D50, whether the polyimide film is prepared by the multi-layer coating method, the PI film is prepared by the PAA method, or the PI film is prepared by the PI solution, the conductive properties of the graphene-like flaky powder material finally obtained are similar. This indicates that the preparation method of the polyimide film has no significant effect on the conductive properties of the graphene-like flaky powder material, which is mainly related to the thickness of the single-layer polyimide film.
[0167] In addition, in the same embodiment, the conductivity of the graphene-like powder material is close to that of the two different particle sizes D50, which indicates that D50 is not the main factor determining the graphene-like flaky powder material. That is, when the thickness of the single-layer polyimide film used is the same, only the particle size D50 of the powder material is changed, and the conductive properties of the graphene-like flaky powder material do not change significantly.
[0168] In order to make the graphene-like flaky powder material more suitable for the conductive powder material in the market, the particle size D50 of the graphene-like flaky powder material is preferably 1.5-15 μm, more preferably about 10 μm.
[0169] Example 15 and Example 16 are other processes for preparing graphite-like flake powders. It is found that changing the order of the powder making process has no significant effect on the conductive properties of the graphite-like flake powder material. The powder making process can be after the polyimide film, after the carbonization process, or even after the graphitization process.
[0170] Compared with Examples 1-16, the thickness of the single-layer polyimide film used in Comparative Examples 1-3 is different, the obtained graphite powder does not have a flaky structure, and the conductivity also changes accordingly. When the thickness of the single-layer polyimide film increases to 20 μm, 50 μm or even 100 μm, at a specific particle size D50, the conductivity of the graphite powder is significantly reduced, showing that the greater the thickness of the single-layer polyimide film, the lower the conductivity of the graphite powder. When the thickness of the single-layer polyimide film is 100 μm, the conductivity of the graphite powder is reduced to about 40 S / cm.
[0171] It can be seen that the thickness of the single-layer polyimide film has a key influence on the structure and conductive properties of the graphene-like flaky powder material. The thickness of the polyimide film can affect the microstructure of the graphene-like flaky powder material, thereby affecting the conductive properties. When the thickness of the polyimide film exceeds twice the particle size D50 of the graphene-like flaky powder material (i.e., 20 μm), the powder material no longer has a flaky structure. As the pulverization continues, it will present a three-dimensional structure, but it still has no flaky characteristics.
[0172] In summary, the results in Table 1 show that:
[0173] (1) Under the condition of the same specific particle size D50 of the graphene-like flaky powder material, the thickness of the single-layer polyimide film used has a key influence on the conductive properties of the graphene-like flaky powder material. Under the condition of the same particle size D50, the smaller the thickness of the single-layer polyimide film used, the greater the conductivity of the graphene-like flaky powder material, and the better the conductive properties.
[0174] (2) Under the condition of using a single-layer polyimide film of the same specific thickness, the change in the particle size D50 of the graphene-like flake powder material has no significant effect on the conductive properties of the graphene-like flake powder material within a certain range.
[0175] (3) The thickness of the single-layer polyimide film is the key factor determining the conductivity of the graphene-like flaky powder material, while the preparation process of the polyimide film or the location of the powder making process has no significant effect on the conductivity of the graphene-like flaky powder material.
[0176] Test Example 2
[0177] In order to verify the use of the graphene-like flaky powder material prepared by the preparation method of the present invention, Cabot's Vulcan XC-72 (abbreviated as VXC72) conductive carbon black is selected as the reference material (its conductivity is 12.9S / cm), and the graphene-like flaky powder materials of Examples 1-16 and the graphite powder materials of Comparative Examples 1-3 are doped in the commercially available conductive carbon black VXC72 in sequence, and the doping amount is 10%. The composite conductive powder material is mixed evenly by physical mixing, and the composite conductive powder material is tested for relevant performances, and compared with the conductivity of the commercially available graphene product doped in the commercially available conductive carbon black VXC72 in the same manner. The conductivity detection method is the same as that of Experimental Example 1, and the results are shown in Table 2.
[0178] The calculation formula for conductivity growth rate is: conductivity growth rate = 100% * conductivity increase / original conductivity.
[0179] Table 2 Performance test of composite conductive powder materials
[0180]
[0181]
[0182] The results in Table 2 show that after Vulcan XC-72 conductive carbon black is doped with the corresponding conductive powder material, its conductivity is higher than that of Vulcan XC-72 conductive carbon black (12.9S / cm) without conductive powder, indicating that the conductive powder has a certain effect on improving the conductivity of Vulcan XC-72 conductive carbon black. It can be found that the thickness of the single-layer polyimide film has a direct effect on the conductivity value of the composite conductive powder material after doping. Under the condition of a specific particle size D50, the smaller the thickness of the single-layer polyimide film, the higher the conductivity of the composite conductive powder material after doping. However, judging only from the conductivity of the composite conductive powder after doping, the conductivity of Vulcan XC-72 conductive carbon black increases before and after doping by 10%, but the change is not very significant. It is mainly considered that it has a great relationship with the doping amount. The greater the doping amount, the greater the conductivity increase. From the perspective of the conductivity growth rate, the thickness of the single-layer polyimide film has a significant effect on the growth of the conductivity of Vulcan XC-72 conductive carbon black.
[0183] In summary, the results in Table 2 show that:
[0184] When the particle size D50 of the graphene-like flake powder material is within a certain range, the thickness of the single-layer polyimide film plays a decisive role in the conductivity of the composite conductive powder material after doping. The smaller the thickness of the single-layer polyimide film, the greater the conductivity of the composite conductive powder material after doping.
[0185] Test Example 3
[0186] (1) Preparation of slurry: The graphene-like flaky powder material obtained in Example 1-16 and the graphite powder obtained in Comparative Example 1-3 are used as the conductive powder to be tested. First, polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) are weighed to prepare a PVDF / NMP solution, and stirred and dispersed in a magnetic stirrer until a transparent slurry is obtained. Then, lithium iron phosphate and the conductive powder to be tested are weighed and ground, and then transferred to the PVDF / NMP slurry, and stirred on a magnetic stirrer for about 12 hours to form a uniform and viscous slurry, wherein the mass ratio of lithium iron phosphate, the conductive powder to be tested and polyvinylidene fluoride is 10:80:10. Pay attention to sealing during the stirring process to prevent the slurry from absorbing water, and all raw materials are dried in a vacuum drying oven before use.
[0187] (2) Preparation of positive electrode sheet: Lay a 12μm thick aluminum foil sheet flat on a glass plate, wipe off the oxide layer on the surface of the aluminum foil, transfer the electrode slurry to the aluminum foil sheet, and use a scraper with a height of 100μm to apply the film at a uniform speed (pay attention to uniform force to avoid the generation of bubbles). After coating, place the coated aluminum foil in an oven at 80℃ for 2h, and then dry it in a vacuum oven at 120℃ for 12h. Then use a cutting machine to cut it into discs with a diameter of 12mm (discard the discs with slurry falling off or impurities), weigh the mass of the discs with an electronic balance, and calculate the mass of the active material. Select the discs with an active material mass difference of less than 0.1mg as positive electrode sheets for the next step of battery assembly.
[0188] (3) Battery assembly: button cell separator, positive electrode shell, negative electrode shell, gasket, spring sheet, 0.45mm smooth lithium sheet as negative electrode sheet, LiPF6 / (EC+DEC) (volume ratio of 1:1, 1mol / L) mixed system as electrolyte, and the prepared positive electrode sheet are used for battery assembly in a vacuum glove box. The glove box needs to be kept full of argon atmosphere and the water and oxygen content are both less than 5ppm. After slightly trimming the lithium sheet, ensure that the order of diameter size is: separator>lithium sheet>positive electrode sheet, the positive electrode sheet, negative electrode sheet and isolation film are wound to obtain a battery cell, and after the battery cell is placed in the packaging shell, the electrolyte is injected and the shell is sealed and assembled, and the lithium battery is packaged with a hydraulic press at a pressure of 500Pa to obtain an electrochemical performance test after standing for 12 hours.
[0189] Test conditions: The test voltage range is 2.5-4.0V. The battery is charged and discharged at 0.2C to detect its first discharge specific capacity.
[0190] At 25°C, charge at 1C constant current to 3.6V, then charge at constant voltage to a current of 0.05C, and then discharge at 1C constant current to 2.0V. Repeat this charge / discharge process to observe the capacity attenuation and calculate the capacity retention rate of the lithium battery after 1000 cycles at 25°C.
[0191] The internal impedance performance of the battery was analyzed by electrochemical impedance spectroscopy (EIS). The EIS was tested using a CHI660e electrochemical workstation with a controlled frequency range of 10 -2 ~10 5 Hz, the scanning speed is 0.1mV / s. The obtained data needs to be fitted using ZView software to obtain the ohmic impedance.
[0192] The results are shown in Table 3.
[0193] Table 3 Battery performance
[0194]
[0195]
[0196]
[0197] The results in Table 3 show that, compared with Comparative Examples 1-3, using the graphene-like flaky powder materials of Examples 1-16 in the positive electrode of the battery can significantly improve the battery's cycle performance and first-cycle discharge capacity, and reduce ohmic impedance. The thickness of the substrate (single-layer polyimide film) of the graphene-like flaky powder material is in the range of 0.1-100 μm. The smaller the thickness, the more beneficial the obtained graphene-like flaky powder material is to improve the cycle performance and first-cycle discharge capacity of the lithium battery and reduce ohmic impedance. When the thickness of the single-layer polyimide film is within a certain range, the D50 of the obtained graphene-like flaky powder material has no significant effect on the battery's cycle performance, first-cycle discharge capacity and ohmic impedance.
[0198] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a graphene-like flaky powder material derived from a polyimide film, characterized in that: The following steps are involved: The polyimide film is post-processed to obtain a graphene-like flaky powder material, wherein the post-processing includes carbonization, graphitization and powder making; the thickness of the polyimide film is 0.1-10 μm.
2. The preparation method according to claim 1, characterized in that: The thickness of the polyimide film is 0.1-5 μm, preferably 0.1-3 μm, more preferably 0.1-1 μm, and most preferably greater than or equal to 0.1 μm and less than 1 μm.
3. The preparation method according to claim 1, characterized in that: The D50 of the graphene-like flaky powder material is 0.2-50 μm, preferably 0.2-30 μm.
4. The preparation method according to claim 3, characterized in that: The D50 of the graphene-like flaky powder material is 1.0-15 μm.
5. The preparation method according to claim 1, characterized in that: The method for preparing the polyimide film is to prepare the polyimide film by a single-layer method or a multi-layer method, and the steps of preparing the polyimide film by the single-layer method include: The diamine monomer and the dianhydride monomer are dissolved in a non-protonic organic solvent to react to obtain a polyamic acid solution, and the polyamic acid solution is cast, dried and imidized to obtain a single-layer polyimide film; Alternatively, a diamine monomer and a dianhydride monomer are dissolved in a solvent, and then a catalyst and a dehydrating agent are added to react to obtain a polyimide solution, and the polyimide solution is cast and dried to obtain a single-layer polyimide film; The steps of preparing the polyimide film by the multilayer method include: 1) preparing a single-layer polyimide film according to the preparation steps of the single-layer polyimide film; 2) coating a release agent on the surface of the single-layer polyimide film; preparing a single-layer polyimide film on the surface of the release agent according to step 1); 3) Repeat step 2) to obtain a multi-layer polyimide film.
6. The preparation method according to claim 5, characterized in that: The method for preparing the polyimide film is to prepare the polyimide film by a multilayer method, wherein the thickness of a single-layer polyimide film is less than 1.0 μm.
7. The preparation method according to claim 1, characterized in that: The carbonization is carried out under vacuum conditions at a temperature of 1100-1400°C.
8. The preparation method according to claim 1, characterized in that: The graphitization is carried out in an inert gas at a graphitization temperature of 2400-3300°C.
9. A graphene-like flaky powder material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the graphene-like flaky powder material prepared by the preparation method according to any one of claims 1 to 8 in electronic devices or batteries.
Citation Information
Patent Citations
A highly graphitized polyimide-based graphite thick film and its preparation method
CN111470876B
High-graphitization graphite thick film and preparation method thereof
CN113184842A
Polyimide film, preparation method thereof and graphite film
CN114437349A
High-thermal-conductivity wave-absorbing graphene composite film prepared from PI films, and preparation method of graphene composite film
CN109264697A
Method for preparing gallium nitride single crystal substrate by using multilayer two-dimensional crystal mask
CN115579280A